2022
DOI: 10.3390/healthcare10010167
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Clinical Characteristics Associated with Improvements in Quality of Life for Participants with Opioid Use Disorder

Abstract: Background: The Houston Emergency Opioid Engagement System was established to create an access pathway into long-term recovery for individuals with opioid use disorder. The program determines effectiveness across multiple dimensions, one of which is by measuring the participant’s reported quality of life (QoL) at the beginning of the program and at successive intervals. Methods: A visual analog scale was used to measure the change in QoL among participants after joining the program. We then identified sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Although the instrument was not used in this study when the patients entered the MMT, given the unfortunate conditions in which they began the program, the eighth week of treatment clearly showed that the patients' quality of life was not as deplorable as it may have been when starting rehabilitation. The worst scoring dominion for the patients was interpersonal relationships, consistent with the findings of other studies [49][50][51]. However, it remains concerning that the highest dropout rates in MMT programs exist among socially isolated individuals.…”
Section: Discussionsupporting
confidence: 88%
“…Although the instrument was not used in this study when the patients entered the MMT, given the unfortunate conditions in which they began the program, the eighth week of treatment clearly showed that the patients' quality of life was not as deplorable as it may have been when starting rehabilitation. The worst scoring dominion for the patients was interpersonal relationships, consistent with the findings of other studies [49][50][51]. However, it remains concerning that the highest dropout rates in MMT programs exist among socially isolated individuals.…”
Section: Discussionsupporting
confidence: 88%
“…19 A study conducted in 2022 reports that people who relapsed during treatment of OUD experienced minor increases in QoL, and participants who attended professional counselling experienced the largest increases in QoL compared with those who did not. 20 There is a lot of literature about OUD and QoL; however, no review elucidates the relationship between QoL and the relapse of OUD. Therefore, the purpose of this study is to review findings about the relationship between QoL and relapse of OUD.…”
Section: Open Accessmentioning
confidence: 99%
“…Individuals with greater improvements in QoL’s health, substance use and emotional health domains were less likely to relapse 19. A study conducted in 2022 reports that people who relapsed during treatment of OUD experienced minor increases in QoL, and participants who attended professional counselling experienced the largest increases in QoL compared with those who did not 20. There is a lot of literature about OUD and QoL; however, no review elucidates the relationship between QoL and the relapse of OUD.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic disease paradigm of integrated medical, behavioral, and social assistance is beneficial for patients with substance use disorders since it is recognized as a chronic illness that negatively affects their quality of life. There is evidence that substance abuse is linked to lower quality of life [ 9 ]. Substance abuse is linked to reductions in many different areas of QoL, such as physical, social, psychological, labor, scholastic, and financial functioning.…”
Section: Introductionmentioning
confidence: 99%